Digital technologies in higher education at distance: mapping and use by the tutors at the Pedagogical University of Mozambique - Tumbo, DionÃsio LuÃs (Cadernos de Educação Tecnologia e Sociedade, 2018)
Today the human being assumes a nomadic position in a ubiquitous society. It inhabits at the same time hyperspaces, characterized by the fluidity of communication mediated by emerging technologies of fast connection to the wireless networks, which contribute to interaction between people from both town and the small and little known village, even in the condition of displacement and ubiquity. The communicational ecologies in fluid spaces in hypermobility are a relevant aspect for the pedagogical use of Digital Information and Communication Technologies (DICT) in Distance Education (DE) since pedagogical actors, although geographically dispersed, can interact with each other. This study focuses mainly on the mapping and description of the pedagogical use of DICTs by the specialized tutors of the courses taught at EaD at the Pedagogical University of Mozambique - Delegation of Niassa (UPNI). For the empirical research, a survey was consciously and voluntarily answered by 30 tutors, 13 of which were from the AMA-Administration and Management Education, 11 from the BE-Basic Education course and 6 from the ET-English Teaching course. Among the participants in the survey half (50%) have between 31 to 40 years old. The results indicate high levels of satisfaction in terms of overcoming digital primary division rates and digital divide characterized by the possession by the subjects of the main computing devices and telecommunications with Internet access, access whose frequency ranges from weekly to daily. Considerable digital literacy was also observed in the use of digital technologies connected to the web through the exploration of software and web services by the participants, indicators evaluated as relevant for the pedagogical use of DICT in courses offered in the modality of Distance Education and more correlated to the cyberculture's time.